Analysis of the Influence of Capital and Production Cost’s on MSME Income - Ezra Aufa Razqa; Doni Andrian; Muhammad Fadly; Sanusi Ghazali (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research uses a descriptive qualitative approach to understand the relationship between capital, production costs, and income of MSMEs based on the experience and perspective of an entrepreneur. The subjects of this research are the owners or managers of MSMEs engaged in various sectors, such as food, crafts, and trade. The data collection techniques in this research used interviews, observation, and documentation techniques. This research data analysis technique uses data reduction, data presentation and conclusion drawing. This research shows that capital management and production cost efficiency play an important role in determining the income of MSMEs, adequate capital support allows entrepreneurs to increase their production capacity and quality, while efficient production cost management ensures the sustainability of a business. External factors, such as accessing and utilizing technology, are also something that can drive the success of MSMEs.